Cardiac fibrosis and dysfunction in experimental diabetic cardiomyopathy are ameliorated by alpha-lipoic acid - Li, Chun-jun (BioMed Central, 2012)
BACKGROUND: Alpha-lipoic acid (ALA), a naturally occurring compound, exerts powerful protective effects in various cardiovascular disease models. However, its role in protecting against diabetic cardiomyopathy (DCM) has not been elucidated. In this study, we have investigated the effects of ALA on cardiac dysfunction, mitochondrial oxidative stress (MOS), extracellular matrix (ECM) remodeling and interrelated signaling pathways in a diabetic rat model. METHODS: Diabetes was induced in rats by I.V. injection of streptozotocin (STZ) at 45 mg/kg. The animals were randomly divided into 4 groups: normal groups with or without ALA treatment, and diabetes groups with or without ALA treatment. All studies were carried out 11 weeks after induction of diabetes. Cardiac catheterization was performed to evaluate cardiac function. Mitochondrial oxidative biochemical parameters were measured by spectophotometeric assays. Extracellular matrix content (total collagen, type I and III collagen) was assessed by staining with Sirius Red. Gelatinolytic activity of Pro- and active matrix metalloproteinase-2 (MMP-2) levels were analyzed by a zymogram. Cardiac fibroblasts differentiation to myofibroblasts was evaluated by Western blot measuring smooth muscle actin (α-SMA) and transforming growth factor–β (TGF-β). Key components of underlying signaling pathways including the phosphorylation of c-Jun N-terminal kinase (JNK), p38 MAPK and ERK were also assayed by Western blot. RESULTS: DCM was successfully induced by the injection of STZ as evidenced by abnormal heart mass and cardiac function, as well as the imbalance of ECM homeostasis. After administration of ALA, left ventricular dysfunction greatly improved; interstitial fibrosis also notably ameliorated indicated by decreased collagen deposition, ECM synthesis as well as enhanced ECM degradation. To further assess the underlying mechanism of improved DCM by ALA, redox status and cardiac remodeling associated signaling pathway components were evaluated. It was shown that redox homeostasis was disturbed and MAPK signaling pathway components activated in STZ-induced DCM animals. While ALA treatment favorably shifted redox homeostasis and suppressed JNK and p38 MAPK activation. CONCLUSIONS: These results, coupled with the excellent safety and tolerability profile of ALA in humans, demonstrate that ALA may have therapeutic potential in the treatment of DCM by attenuating MOS, ECM remodeling and JNK, p38 MAPK activation.